Navigating the Phenotype Frontier: The Monarch Initiative. Issue 4 (1st August 2016) - McMurry, Julie A; Köhler, Sebastian; Washington, Nicole L; Balhoff, James P; Borromeo, Charles; Brush, Matthew; Carbon, Seth; Conlin, Tom; Dunn, Nathan; Engelstad, Mark; Foster, Erin; Gourdine, Jean-Philippe; et al.
Abstract: The principles of genetics apply across the entire tree of life. At the cellular level we share biological mechanisms with species from which we diverged millions, even billions of years ago. We can exploit this common ancestry to learn about health and disease, by analyzing DNA and protein sequences, but also through the observable outcomes of genetic differences, i.e. phenotypes. To solve challenging disease problems we need to unify the heterogeneous data that relates genomics to disease traits. Without a big-picture view of phenotypic data, many questions in genetics are difficult or impossible to answer. The Monarch Initiative (https://monarchinitiative.org ) provides tools for genotype-phenotype analysis, genomic diagnostics, and precision medicine across broad areas of disease.